2014
DOI: 10.1517/17425247.2014.919253
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: review on therapeutic potential and recent advances in drug delivery

Abstract: Resveratrol demonstrated its ability to be a potential drug candidate for the treatment of different ailments due to its potent antioxidant properties. To improve the drug stability, increase the bioavailability and minimize side-effects of resveratrol, novel drug delivery systems have been formulated to bring this potential candidate to the first line of disease treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
153
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(162 citation statements)
references
References 124 publications
0
153
0
2
Order By: Relevance
“…Despite there is extensive information on stilbene activities against plant fungal pathogens (see above) and Planta (2017) 246:597-623 609 human microbial pathogens (Pangeni et al 2014), there are scarce reports on stilbene activities and accumulation in response to phytopathogenic bacteria. Maddox et al (2010) reported that 12 phenolic compounds, including stilbenes, inhibited growth of a plant pathogenic bacterium, Xylella fastidiosa, isolated from grape and almond.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite there is extensive information on stilbene activities against plant fungal pathogens (see above) and Planta (2017) 246:597-623 609 human microbial pathogens (Pangeni et al 2014), there are scarce reports on stilbene activities and accumulation in response to phytopathogenic bacteria. Maddox et al (2010) reported that 12 phenolic compounds, including stilbenes, inhibited growth of a plant pathogenic bacterium, Xylella fastidiosa, isolated from grape and almond.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…1), such as pterostilbene, oxyresveratrol, or viniferins, are the most famous stilbenes due to their diverse potent biological activities and medicinal properties and have been extensively studied (Kalantari and Das 2010;Pangeni et al 2014;Estrela et al 2013;Xu et al 2014;Wang and Yao 2015). Resveratrol has been shown to possess antioxidant, immunomodulatory, anti-inflammatory, and antiangiogenic effects and a wide range of health benefits, such as cancer chemoprevention or cardioprotection (Kalantari and Das 2010;Pangeni et al 2014;Weiskirchen and Weiskirchen 2016). A number of other stilbenoids ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…They aroused a huge interest in scientists after being identified in wine and linked to the "French paradox" and are mainly present in grape skin, but also in seeds, clusters, and stems (Katalinić et al, 2010). Thus, a big number of reviews confirming resveratrol's biological activities are present in the literature (Athar et al, 2007;Baxter, 2008;Smoliga et al, 2011;Pangeni et al, 2014). Due to their biological and organoleptic characteristics, anthocyanins and stilbenes play a key role in wine quality, and grape extracts are used as sources of natural compounds in the pharmaceutical, food and nutraceutical industries (Flamini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite over 70% of resveratrol taking orally is absorbed across the gastrointestinal epithelium, the oral bioavailability is less than 1% because of rapid and extensive first pass metabolism mainly by Phase II metabolic reaction to sulfate and glucuronide conjugates [22,23]. It is not water soluble and also chemically unstable which requires development of custom designed formulation optimized specifically for resveratrol to enhance its oral delivery such as using micro-and nano-encapsulation with suitable carriers [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is not water soluble and also chemically unstable which requires development of custom designed formulation optimized specifically for resveratrol to enhance its oral delivery such as using micro-and nano-encapsulation with suitable carriers [22]. It is also a substrate of efflux transporter proteins such as MRP2, MRP3, and ABCG2 which could further limit its gastrointestinal absorption and intracellular concentrations [24].…”
Section: Introductionmentioning
confidence: 99%